Jigsaw Learning VS Student Team Achievement Divisions (STAD): Which One is Better in Improving Learning Outcomes - Fatihannisa, Fadhilah; Suhandini, Purwadi; Suminar, Tri (Journal of Primary Education)
Social study is an essential subject for intellectual, emotional, cultural and social development for students, namely being able to develop responsible ways of thinking, behaving and behaving as individuals and citizens. The average cognitive results of students from the four schools based on midterm exam (UTS) I scores only 35.4% of students completed, while the rest were failed.The purpose of this study was to determine the differences oflearning outcomes between the Jigsaw learning model and Student Team Achievement Division (STAD) in the cognitive, affective and psychomotor domains. This comparative experimental study uses a pre-test?post-test comparations group design. The data collection tool uses test instruments and non-tests with quantitative data analysis techniques. The cognitive domains of students were measured using test instruments, including pre-test and post-test questions, while to measure affective, and psychomotor were measured using non-test instruments in the form of student observation sheets. The results of this study show that there is no difference increase in cognitive learning outcomes of students taught using Jigsaw and STAD learning models, but there are differences for affective and psychomotor domains. The Jigsaw learning model is more effective in improving social studies learning outcomes compared to that of the learning model (STAD). The highest score of Jigsaw in the cognitive domain is 84.17, and the affective domain is 64.17, but the lowest score of Jigsaw in the psychomotor domain is 63.09. The advantages of STAD in the psychomotor domain is 81.40, but in the affective domain is 59.58, based on learning outcomes in social studies students.